Influence of limb physiotherapy and maintenance of bronchial hygiene on level of consciousness in head injury - A.Jadhav, Ankita; B.Kanase, Suraj (International Journal of Psychosocial Rehabilitation, 2020)
Background: The present rate of hospitalization for head injury is high nowadays. Many patients die in a coma state; some patients become severely disabled or remain in a vegetative state. There are many nosocomial infections seen in prolonged hospital stay conditions. Till now a strong correlation of limb physiotherapy along with bronchial hygiene as coma arousal is yet to be established.Methods—A total of 87 head injury subjects with Glasgow Coma Scale scores below 8 were included by using a convenient sampling method. Pre-intervention assessments were done with GCS and CPIS. The subjects were given limb physiotherapy and bronchial hygiene techniques for 7 days. Statistical analyses were done with appropriate tools.Result—Post value of GCS is 7.759 ± 2.023 and CPIS is 5.402 ± 1.728, which showed a significant effect of limb physiotherapy along with maintained bronchial hygiene on level of consciousness in head injury.Conclusion—This study concluded that limb physiotherapy and maintained bronchial hygiene have a significant effect on improving the consciousness level of head injuries.